Diamond‐Based All‐Carbon Photodetectors for Solar‐Blind Imaging. Issue 15 (29th May 2018) - Lin, Chao‐Nan; Lu, Ying‐Jie; Yang, Xun; Tian, Yong‐Zhi; Gao, Chao‐Jun; Sun, Jun‐Lu; Dong, Lin; Zhong, Fang; Hu, Wei‐Da; Shan, Chong‐Xin
Abstract: Single‐crystalline diamond wafers are synthesized, and all‐carbon solar‐blind photodetectors are constructed based on the diamond with interdigitated graphite as electrodes. The graphite electrodes are made by laser‐induced graphitization of the diamond. The peak responsivity of the photodetector is 21.8 A W −1, and detectivity is 1.39 × 10 12 cm Hz 1/2 W −1 when the bias voltage is 50 V, it is noted that both of these are among the best values ever reported for diamond‐based photodetectors. The photodetectors are employed as the sensing pixels in an imaging system, and a clear image is obtained, which is the first report on solar‐blind imaging of diamond photodetectors. The results reported in this paper provide a facile approach to high‐performance diamond solar‐blind photodetectors and their applications in solar‐blind imaging, thus may address a significant step toward the preparation and application of diamond photodetectors. Abstract : All‐carbon solar‐blind photodetectors are constructed based on single‐crystalline diamond with interdigitated graphite as electrodes, which are realized by laser‐induced local graphitization of the diamond. The photodetectors can be employed as the sensing pixels in an imaging system, and a clear image is obtained, which is the first report on solar‐blind imaging of diamond‐based photodetectors.